2019
DOI: 10.26480/jwbm.02.2019.09.13
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Solid Waste Management Practices in Lamjung District Community Hospital, Nepal

Abstract: This study assessed the process of managing the health care wastes and their disposal in one of the major hospital in Lamjung district, Nepal. It was found that the hospital does not quantify solid wastes and segregation of the different types of wastes is not so well practiced. Average awareness of the magnitude of hospital waste management of hospital staffs and patients ages ranging from 15 to 85 was found at 67.857% and 49% respectively. The findings in this paper indicated that the waste generation rate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Hospital waste, obsolete pesticides, and a few industrial wastes were the most common sources of hazardous waste in BM. It was reported that the waste generated by one of the biggest hospitals in Lamjung in BM was 141.765 kg/day, consisting of 91.94% nonhazardous waste and 8.060% hazardous waste [ 3 ]. In BM, most hospitals, health posts, and health clinics did not have incinerators.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospital waste, obsolete pesticides, and a few industrial wastes were the most common sources of hazardous waste in BM. It was reported that the waste generated by one of the biggest hospitals in Lamjung in BM was 141.765 kg/day, consisting of 91.94% nonhazardous waste and 8.060% hazardous waste [ 3 ]. In BM, most hospitals, health posts, and health clinics did not have incinerators.…”
Section: Resultsmentioning
confidence: 99%
“…Target 3.9 refers to reducing the number of deaths and diseases due to hazardous chemicals, pollution, and contamination of air, water, and soil [ 13 ]. Aryal et al [ 3 ] reported that medical waste disposal in BM is often problematic. It is important to properly manage medical waste within health facilities, such as by incineration, sterilization, or shredding, to reduce the spread of infections and pathogens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation